USM RESEARCHERS DISCOVER MOST COMPREHENSIVE BLUEPRINT FOR RUBBER PRODUCTION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 28 June 2016 A collaboration between researchers from Universiti Sains Malaysia (USM) and their partners from RIKEN Centre for Sustainable Resource Science (CSRS) Japan has resulted in them becoming the world's first in discovering the most comprehensive blueprint of genome sequences for natural rubber (Hevea brasiliensis).